Pengembangan Perangkat Pembelajaran Berbasis Budaya Banten Pada Tema 2 Di Kelas 5 Sekolah Dasar - Ihda Fahyarulwaro Sarta; Sri Wuryasturi (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research was conducted to develop a learning device based on Banten culture. As mandated by the 2013 curriculum, introducing cultural values can shape the characteristics of students. Science is a natural learning concept and has a very broad relationship related to human life and nature. Science learning plays a very important role in the educational process and also the development of science learning technology is expected to be a vehicle for students to learn about themselves and the natural environment and further development of application in everyday life. Researchers use Baduy culture in developing learning tools that will be integrated in thematic learning, namely theme 2 clean air for health and sub-theme 2 the importance of clean air for breathing in learning 1 in grade 5. This research and development method or Research and Development (RnD) is guided by the ADDIE model which uses 5 stages, namely: analyze, design , development, implementation, and evaluation. The product developed in this study is a Learning Implementation Plan (RPP) consisting of Teaching Materials, Student Worksheets (LKPD), and Test Instruments (Grids, Test Questions, Scoring Guidelines, and Answer Keys). The subjects in this study were 5th graders at SDN Buah Gede with a total of 14 students. Qualitative data in this study were obtained from observations and interviews. The feasibility of the product developed through validation by material experts and evaluation experts. The results of the validation of RPP, Teaching Materials, LKPD get a percentage of 85.01-100.00% and Instrument Tests get a percentage on the material component of the question with a score of 90% (Very Valid), the component of the assessment form with a score of 91% (Very Valid) and the Language component used 75% (Sufficiently Valid). In this case the validity of the product developed is feasible to use.